2019
DOI: 10.3168/jds.2018-15038
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and genomics of reproductive disorders in Canadian Holstein cattle

Abstract: In Canada, reproductive disorders known to affect the profitability of dairy cattle herds have been recorded by producers on a voluntary basis since 2007. Previous studies have shown the feasibility of using producer-recorded health data for genetic evaluations. Despite low heritability estimates and limited availability of phenotypic information, sufficient genetic variation has been observed for those traits to indicate that genetic progress, although slow, can be achieved. Pedigree-and genomic-based analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 66 publications
4
45
0
1
Order By: Relevance
“…We also found two genes (CTNNBIP1 and NMNAT1) to be related to reproductive efficiency. CTNNBIP1 has been previously reported to be related to prenatal death in Nordic Red [64] and retained placenta in Canadian Holstein dairy cows [65]. NMNAT1 was found to affect age at first calving in Nellore cattle [66], and this gene was also implicated in influencing the female reproductive efficiency in cattle [67].…”
Section: Discussionmentioning
confidence: 91%
“…We also found two genes (CTNNBIP1 and NMNAT1) to be related to reproductive efficiency. CTNNBIP1 has been previously reported to be related to prenatal death in Nordic Red [64] and retained placenta in Canadian Holstein dairy cows [65]. NMNAT1 was found to affect age at first calving in Nellore cattle [66], and this gene was also implicated in influencing the female reproductive efficiency in cattle [67].…”
Section: Discussionmentioning
confidence: 91%
“…The WssGBLUP has been successfully applied to several genomic prediction studies (Zhang et al, 2016;Lourenco et al, 2017;Guarini et al, 2019). However, to our best knowledge, there are no reports evaluating the prediction ability of WssGBLUP in crossbred animals, especially in F1 populations.…”
Section: Introductionmentioning
confidence: 99%
“…PIK3R1 , ITK and TMEM173 were identified as potential positional candidate genes associated with infection of Mycobacterium avium subspecies paratuberculosis in cattle [ 40 42 ]. A study reported that the MTSS1 was related to metritis in cattle [ 43 ]. Guangxi Zhuang Autonomous Region undergoes characteristic subtropical monsoon climate with hot and humid summers and dry and mild winters, which provides an environment for the spread of disease.…”
Section: Discussionmentioning
confidence: 99%